Pengaruh Model Kooperatif Tipe Teams Games Tournament (TGT) Berbantuan Media Spinning Wheel Terhadap Pemahaman Konsep IPAS Sekolah Dasar - Amelia Rahmawati; Asep Deni Normansyah; Nurul Fazriyah (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2026)
This study aims to determine the effect of the Teams Games Tournament (TGT) cooperative learning model assisted by the Spinning Wheel media on the understanding of science concepts in fourth-grade elementary school students. This study uses a quantitative method with a quasi-experimental design. Data collection uses a concept understanding test. The sample used in this study were fourth-grade elementary school students. The results showed that the average initial concept understanding test score of the experimental class was 47.75, higher than the average initial concept understanding test score of the control class (47.32). After treatment, the average final concept understanding test score of the experimental class was 90.00, higher than the average final concept understanding test score of the control class (85.00). Researchers used an Independent Samples T-Test to determine the effect of the learning model. The results of the Independent Samples T-Test showed a significance value of 0.003 <0.05, and the results of the effect size test obtained a value of 0.828, which is considered large. Based on the research results, it can be concluded that: 1) the process of implementing the Team Game Tournament (TGT) model assisted by the spinning wheel media is very effective and can make learning more meaningful; 2) there is a significant difference with a large influence between the experimental class and the control class on students' understanding of science concepts; and 3) the use of the cooperative Team Game Tournament (TGT) model assisted by the spinning wheel media has a significant and large influence on the understanding of science concepts of fourth grade elementary school students.